2015
DOI: 10.18488/journal.90/2015.2.2/90.2.24.36
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Sport Education Model on University Students Game Performance and Content Knowledge in Basketball

Abstract: Many universities offer an abundant amount of physical activity courses designed to improve Contribution/ OriginalityThis study is one of very few studies which have investigated the impact of the Sport Education model on a university physical activity course. Findings suggest that the model can have a positive effect on game performance and sport content knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…According to the results of the study conducted by Mohr et al (2006) to determine the effect of the sports education model on sports knowledge; in the basketball contents knowledge scores conducted during the middle of the study and at the end of the study, significant differences were obtained in favor of the final test in the group, and in favor of the sports education model amongst the groups, and it was determined that the sports education model was an effective educational approach to gaining content knowledge. The findings of the study by Layne and Piipari (2015) show that the sports education model is an effective pedagogical approach to improve the game performance and sports content knowledge of undergraduate students. According to the study conducted by Çelen (2012) about the cognitive domain, there is a statistically significant difference between the cognitive domain pre-test and post-test values of the control and experimental groups for the volleyball course in favor of the post-test values, and that when the beginning and end behaviors of the experimental and control group students were compared, a significant increase in favor of end behavior was recorded.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
“…According to the results of the study conducted by Mohr et al (2006) to determine the effect of the sports education model on sports knowledge; in the basketball contents knowledge scores conducted during the middle of the study and at the end of the study, significant differences were obtained in favor of the final test in the group, and in favor of the sports education model amongst the groups, and it was determined that the sports education model was an effective educational approach to gaining content knowledge. The findings of the study by Layne and Piipari (2015) show that the sports education model is an effective pedagogical approach to improve the game performance and sports content knowledge of undergraduate students. According to the study conducted by Çelen (2012) about the cognitive domain, there is a statistically significant difference between the cognitive domain pre-test and post-test values of the control and experimental groups for the volleyball course in favor of the post-test values, and that when the beginning and end behaviors of the experimental and control group students were compared, a significant increase in favor of end behavior was recorded.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
“…The students describe their ideal coach in the following way: the coach describes the team's future perspectives after each successful competition; he is open for the new ideas and propositions that come from the students; he patiently teaches the players and responds to all their questions; he regularly increases his skills and abilities level (Su & Han, 2017). The need for the knowledge improvement among the practicing coaches and making the corrections in the future coaches' training program are the compulsory elements of the professional basketball players' eff ective training system organization (Layne & Yli-Piipari, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Research in physical education (Hastie, Sinelnikov, & Guarino, 2009;Hastie, Calderón, Rolim, & Guarino, 2013;Layne & Yli-Piipari, 2015) has shown that an increased opportunity for practice during a Sport Education season may lead to gains in skill and match performance, which also often is the main focus in youth sport. Although one primary goal of Sport Education is to develop competent sport persons, the current study did not measure player skill or match performance.…”
Section: Jan-erik Romar Jani Sarén Peter Hastiementioning
confidence: 99%